Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, Pengeluaran Konsumsi Rumah Tangga Untuk Makanan, Pengeluaran Konsumsi Rumah Tangga Untuk Non Makanan, Dan Jumlah Penduduk Terhadap Indeks Pembangunan Manusia Provinsi Bali - Erwin Ndakularak (Universitas Kristen Wira Wacana Sumba, 2015)
Implementation of autonomy region means that the local goverment must be able to run more efficient and effective governmental administration, democratic and encourage society roles, implement of justice and equality in society, and able to develop th whole potency owned by the region and its society in order to implement prosperity and development of the region. The purpose of this research is to see the influence of Local Revenue Income, balance budgets, expenditure of household consumption, and total population to HDI in Bali Province.Keyword: Local Revenue Income, Balance Budgets, Consumption Household, and Total Population